Cognitive dysfunction after isolated brain stem insult. An underdiagnosed cause of long term morbidity. Issue 2 (1st August 2002) - Garrard, P; Bradshaw, D; Jäger, H R; Thompson, A J; Losseff, N; Playford, D
Abstract : Cognitive dysfunction adversely influences long term outcome after cerebral insult, but the potential for brain stem lesions to produce cognitive as well as physical impairments is not widely recognised. This report describes a series of seven consecutive patients referred to a neurological rehabilitation unit with lesions limited to brain stem structures, all of whom were shown to exhibit deficits in at least one domain of cognition. The practical importance of recognising cognitive dysfunction in this group of patients, and the theoretical significance of the disruption of specific cognitive domains by lesions to distributed neural circuits, are discussed.